FAKTOR DOMINAN YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS IMMINENS - Hamidah Hamidah; Siti Masitoh (Jurnal Ilmu dan Teknologi Kesehatan, 2013)
Abortion imminens is bleeding spots that indicate a threat to the viability of a pregnancy. Imminens abortion complications in the form of bleeding or infectioncan cause death. The purpose of this study to determine the factors associated with the incidence of abortion in the department of Ciptomangunkusumo imminens. This research using cross-sectional observational survey. The sample is all women who experience bleeding in pregnancy were treated in the inpatient department of Madura with inclusion and exclusion criteria that have been established and recorded in the medical record. The results obtained bivariate analysis age, parity, gestational age and miscarriage associated with abortion imminens. While the education variable was not associated with abortion imminens. The results of multivariate analysis, suggesting that parity> 3 risk 6.9 times greater than parity 1-3. Age <20 and> 35 years of risk 4 times greater than 20-35 years of age and miscarriage risk 4.2 times greater than ibuyang no history of abortion. Therefore, the parity is the dominant risk factor on the incidence of abortion imminens. Health workers, particularly midwives to further enhance the knowledge and skills, in order to detect early abortion imminen possibility that complications could be solved properly.